MENELUSURI BANGUNAN EPISTEMOLOGI KEISLAMAN KLASIK (Epistemologi Bayani, Burhani dan Irfani) - ., Mutakallim (Jurnal Pendidikan Kreatif, 2020)
Bayani is an epistemology which assumes that the source of knowledge is revelation (text) or reasoning from the text. Burhani epistemology believes that the source of knowledge is reason. While ‘Irfani is an epistemology which assumes that science is the will (iradah). The chronology of Bayani at least has begun from Prophet Muhammad era when he explained difficult verses for friends to understand. Then, the friends interpreted it. Tabi'in collected texts from Rasulullah SAW and friends. They attached their interpretation and their ability of reasoning and ijtihad with the text as the main guidance. Aristoteles was the first person to develop Burhani epistemology which more focused on epistemological values than formal logic. The sources of ‘Irfani were divided into several classifications which in author's point of view, it was not from outside Islam because it was about the life of Allah’s Messenger. Prophet's friends and Tabi'in intended to use and to practice ‘Irfani even though the naming had not yet existed. The superiority of Bayani lies in the correctness of the text (the Qur’an and the Hadith) as the main source of universal Islamic law so that it becomes a guide and benchmark. However, its limitation lead to stagnation in religious life because its inability to respond the current development. Whereas the strength of Burhani is the system of thinking for epistemological construction which is built on reasoning and logic but it is sometimes limited of asynchronous texts and reality. The strength of ‘Irfani is all the knowledge from intuitions, musyaadah and mukasyafah are closer to the truth of sciences which are extracted from rational arguments and reasons. The weakness of Irfani is it can only be enjoyed by specific people who are able to reach a high level of self-purification and are very subjective in judging things based on their individual experience.